Modulation of frontogenetic plankton production along a meandering jet by zonal wind forcing: An application to the Alboran Sea. Issue 8 (24th August 2017) - Oguz, Temel; Mourre, Baptiste; Tintoré, Joaquin
Abstract: We present a coupled physical‐biological modeling study to elucidate the changes in ageostrophic frontal dynamics and the frontogenetic plankton production characteristics of a meandering jet under the impacts of successive westerly/easterly wind events combined with seasonal variations in the upstream transport and buoyancy flux characteristics of the jet, using a case study for the Alboran Sea (Western Mediterranean). Their nonlinear coupling is shown to result in different forms of physical and biological characteristics of the background jet structure that follows a meandering path around two anticyclonic gyres in the western and eastern basins and a cyclonic eddy in between. The westerly, downfront wind events broaden the jet, and result in stronger cross‐frontal density contrast and intensify ageostrophic cross‐frontal secondary circulation. Thus, they improve the frontogenetic plankton production with respect to the no‐wind case. They also support higher production along the northern coast in response to wind‐induced coastal upwelling and spreading of resulting nutrient‐rich, productive water by mesoscale stirring. These features weaken gradually as the jet transport reduces. In contrast, stronger and longer‐lasting easterlies during the reduced jet transport phase weaken the currents and frontal density structure, change the circular Western Alboran Gyre to an elongated form, and shift the main axis of the jet towards the southern basin. Then, frontogenesis fails to contribute to phytoplankton production that becomes limited to the eddy pumping within cyclones. Apart from the frontogenetic production, eddy pumping, mesoscale stirring, and diapycnal mixing of nutrients support intermittent and localized phytoplankton patches over the basin. Key Points: The westerly (downfront) winds in the direction of the Atlantic Jet improve the frontogenetic plankton production The short‐term (weekly) easterly (upfront) winds introduce only a weak perturbation on the existing plankton production characteristics The stronger and longer‐lasting easterly (upfront) wind events may impose unfavorable conditions for plankton production along the jet